Hakikat Evaluasi dalam Filsafat Pendidikan Islam - Shifa Alya Nafisa; Meyniar Albina (Moral : Jurnal kajian Pendidikan Islam, 2024)
Evaluation in the Philosophy of Islamic Education has a crucial role in measuring the success of the learning process and achieving the educational goals that have been set. This journal examines in depth the nature of evaluation in the perspective of Islamic Philosophy of Education. Through literature review, this study analyzes the concept of evaluation in the Qur'an and Hadith, as well as the thoughts of Islamic education figures. The results of the study show that evaluation in Islamic Education has unique characteristics rooted in Islamic values, such as justice, integrity, and the development of individual potential. In addition, this study also identifies challenges and opportunities in the application of evaluation in the context of modern Islamic education. Evaluation is an assessment process that aims to measure the progress and achievement of students in various aspects of life, including mental-psychological and spiritual-religious aspects. Evaluation in Islamic education aims to ensure that students not only have a religious attitude, but also have the knowledge and skills necessary to do charity and serve God and society. which covers all relevant aspects of life and also involves measuring students' attitudes, moral values, skills, and religious spiritual abilities.